(untitled) (International Journal of Statistics in Medical Research, 2013)
Background: Physical activity self-efficacy is conceptualized as a construct that is changeable and responsive to contextual factors. The current study applied mixed-effects location scale modeling to examine within-person variability in physical activity self-efficacy among middle-aged and older adults (N = 14 adults, mean age = 59.4 years) who were attempting behavior change. Methods: An electronic diary was used to record self-reported self-efficacy and physical activity via Ecological Momentary Assessment (EMA) twice a day (2:00 pm and 9:00 pm). Data from weeks 1-6 were analyzed using a Mixed-Effects Location Scale Model in SAS PROC NLMIXED. Results: Participants differed from each other in the degree to which physical activity self-efficacy varied from day to day (p = .03). Within-person variation in self-efficacy was negatively related to levels of brisk walking each week (p = .002), and decreased over time (p = .03). Conclusions: Preliminary results suggest that fluctuations in self-efficacy may be as important for predicting short-term behavior as the overall or mean level of self-efficacy.